POSSIBILITIES OF LASER RADIATION INTERACTION WITH NANOPARTICLES - RIHAKOVA, Lenka; CHMELICKOVA, Hana (Trends in education, 2014)
This article is focused on the laser treatment of nanoparticles. Using laser radiation nanoparticles can be synthesized by mechanism of ablation. It is also possible to modify their structural and morphological properties. Lasers with short and ultrashort pulses with duration in nano, pico and mainly femtoseconds are widely used in praxis.
Keywords: laser; nanoparticles; synthesis.